Microarray-based comparative genomic analyses of the human malaria parasite Plasmodium falciparum using Affymetrix arrays. - Carret, C; Horrocks, P; Konfortov, B; Winzeler, E; Qureshi, M; Newbold, C; Ivens, A (2005)
Microarray-based comparative genomic hybridization (CGH) provides a powerful tool for whole genome analyses and the rapid detection of genomic variation that underlies virulence and disease. In the field of Plasmodium research, many of the parasite genomes that one might wish to study in a high throughput manner are not laboratory clones, but clinical isolates. One of the key limitations to the use of clinical samples in CGH, however, is the miniscule amounts of genomic DNA available. Here we describe the successful application of multiple displacement amplification (MDA), a non-PCR-based amplification method that exhibits clear advantages over all other currently available methods. Using MDA, CGH was performed on a panel of NF54 and IT/FCR3 clones, identifying previously published deletions on chromosomes 2 and 9 as well as polymorphism in genes associated with disease pathology.